Association of Adiponectin With biochemical parameters in patients with chronic kidney diseases on Hemodialysis process in Erbil city - Jwan Qader Azeez; Dler Qader Gallaly (Zanco Journal of Pure and Applied Sciences, 2023)
Adiponectin (Adipo.) is a hormone produced by adipocytes that circulate in the blood. Serum Adipo. concentrations are elevated in several chronic kidney disease (CKD) conditions and are a predictor of end-stage renal disease. The association between Adipo. levels and the progression of the disease are not well established. This study aimed to determine if there was a relationship between serum Adipo. levels and inflammatory, metabolic, and CKD progression in Erbil. In a case-control study of 200 participants, 100 with CKDs were on hemodialysis (HD) in Erbil teaching hospital. To collect the necessary information from participants, a study questionnaire was used. Adipo. hormone levels and other metabolic parameters were measured. Total Cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL), very-low-density lipoprotein (VLDL), fasting blood sugar, C-reactive protein (CRP), glycosylated hemoglobin (HbA1c), creatinine, albumin, and urea were all measured in the blood. 90.0% of the cases were at stage 5 of CKD, the Serum Adipo. levels were higher when compared with a healthy control group (13.26 ±0.96 µg/ml vs 2.17±0.75 µg/ml). In conclusion, our study found A high level of Adipo. in CKD patients can predict inflammation and malnutrition and is considered a biomarker for renal dysfunction.